2022
DOI: 10.1155/2022/9504150
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Sensitivity and Variability of Agromorphological Traits and Brix Content of Sweet Sorghum Cultivated in Burkina Faso under Two Sowing Dates

Abstract: Sweet sorghum is mainly cultivated for the sweetness of its stems and the quality of its fodder. Unfortunately, its cultivation is gradually being abandoned in Burkina Faso due to climatic hazards. In a general context of strong variations in the rainfall regime, it is, therefore, important to determine the effect of the sowing period on the expression of agromorphological traits and Brix content. Thus, 29 sweet sorghum accessions were evaluated using 15 quantitative variables in a three-replicate Fisher block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Flowering was early and clustered for the genotypes of the three sorghum types studied. These results could be explained by the sensitivity of these sorghums to photoperiod variation as reported by several previous studies [24][25][26].…”
Section: Discussionsupporting
confidence: 76%
“…Flowering was early and clustered for the genotypes of the three sorghum types studied. These results could be explained by the sensitivity of these sorghums to photoperiod variation as reported by several previous studies [24][25][26].…”
Section: Discussionsupporting
confidence: 76%
“…In Burkina Faso, since 2008, many investigations have been undertaken by University of Ouagadougou (current University Joseph Ki-Zerbo) for the sweet stalk sorghum potential. These efforts focused on the characterization of its genetic diversity and the Brix content in the stalk [13][14][15], the evaluation of the photoperiod sensitivity of genotypes [13], and the genetic relationships between this sorghum and other types of sorghum grown [14][15][16]. All of these studies have shown significant genetic diversity within sweet stalk sorghum, high sensitivity to photoperiod, and close genetic proximity among grain sorghum and sweet grain sorghum.…”
Section: Introductionmentioning
confidence: 99%